The effect of the husband’s criminal conviction on the dissolution of the family and the creation of the right to divorce for the wife - Bassami, Masoud (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Divorce is a matter that falls within the rights and prerogatives of the husband. However, Islamic jurisprudence and Iranian law allow a wife to request a divorce in certain cases. One such case is when a husband is criminally convicted to a prison sentence of five years or more, or if he is convicted of a crime that is contrary to the marital interests of the wife. These instances, in addition to being mentioned in Iranian laws, are also included as conditions in marriage contracts. This research aims to determine and analyze the necessary conditions for issuing a divorce verdict at the wife’s request in the case of the husband’s criminal conviction. Method: The present study is conducted using a descriptive-analytical method, and its data have been collected through library research. Results: The findings indicate that in cases where the husband is criminally convicted to a prison sentence of five years or more, or if he is convicted of a crime that is contrary to the marital interests of the wife, and if the wife experiences hardship and distress, she has the right to divorce. Conclusion: The research results suggest that the husband’s criminal conviction alone is not sufficient for a divorce verdict to be issued; additional conditions are also necessary, such that the wife experiences hardship and distress.